Training of Verbal Working Memory at Sentence Level Fails to Show Transfer - Fellman, Daniel; Soveri, Anna; Waris, Otto; Laine, Matti (Frontiers in Communication, 2017)
During the past decades, working memory (WM) training has attracted considerable research attention, but its transfer to untrained tasks is still controversial. In a randomized controlled trial, we investigated the possible transfer effects of a novel sentence-level WM training regime. Sixty-eight healthy Finnish adults were randomized into either a WM training group or an active control group. The WM training group practiced for four weeks with two adaptive sentence-level WM training tasks, namely a novel sentence-level updating task and a reading span task. The active control group practiced on a quiz task that called for long-term memory but did not load on WM. There were no statistically significant training effects on the pre-post measures of near and far transfer. We suggest that the lack of training effects may reflect the specificity and automaticity of the sentence processing system.